The complete mitochondrial genome of Siniperca fortis (Perciformes: Sinipercidae). Issue 2 (2nd April 2020) - Peng, Min; Zhu, Weilin; Zeng, Digang; Yang, Chunling; Chen, Xiuli
Abstract: Siniperca fortis (Perciformes: Sinipercidae) is an endemic species in Zhujiang (Pearl) River system of China. Through genome sequence and phylogenetic analyses, the main structural characteristics of the mitochondrial genome sequence and the phylogenetic information of S. fortis were revealed. In this study, the complete mitochondrial genome of S. fortis was firstly determined. The genome is 16, 495 bp in length and consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region. The genetic distance and the ML Phylogenetic tree of 11 species in Sinipercidae supported that S. fortis was a valid species. The mitochondrial DNA information would be useful in species identification and natural resources conservation.